Functional amyloid-chitin hybrid ink coupled with flexible fabrication approaches for diverse macro and micro-structures. (January 2022) - Wei, Shicao; Li, Yingfeng; Li, Ke; Kang, Anqi; Zhang, Siyu; Feng, Teng; Zhang, Hui; Zhong, Chao
Abstract: The precise fabrication of artificially designed molecular complexes into ordered structures resembling their natural counterparts would find broad applications but remains a major challenge in the field. Here we genetically design chitin-binding domain (CBD)-containing amyloid proteins, and rationally fabricate well-ordered CBD-containing functional amyloid-chitin complex structures by coupling a top-down manufacturing process with a bottom-up self-assembly. Our fabrication approach starts with the dissolution of both CBD-containing functional amyloid and chitin in hexafluoroisopropanol (HFIP) to make a hybrid ink. This hybrid ink platform, coupled with multiple fabrication methods including airbrushing, electrospinning and soft-lithography, produces a series of unique freestanding structures. The structural features of the products, such as the ability to direct the light path and mimicking of the extracellular matrix enable applications in functional light gratings and cell culture, respectively. Further genetic engineering of the protein component allowed tunable functionalization of these materials, including nanoparticle immobilization and protein conjugation, resulting in broad applications in electronic devices and enzyme immobilization. Our technological platform can drive new advances in biocatalysis, tissue engineering, biomedicine, photonics and electronics. Graphical abstract: Image 1